Scaffolding techniques and speaking skill - Almeida Obando, María Esther; Bastidas Guevara, Norma Cecilia; Mantilla Carrera, Paola Nathaly; Solís Mejía , Javier Guillermo; Bejarano Urquizo, Lourdes Elizabeth (Arandu UTIC, 2024)
The use of scaffolding techniques in the classroom help students improve the development of their language skills. The present study aimed to analyze the influence of Scaffolding techniques on the development of speaking skill in students of seventh semester in “Pedagogia de los Idiomas Nacionales y Extranjeros.” The research developed a quantitative approach and it was experimental. The population in the study were 24 students of seventh semester. The instruments used during the investigation were a preand posttest, the researcher used part 3 of B1 preliminary test to assess students before and after the treatments. The treatments consisted on 5 session where the researcher applied scaffolding techniques, additionally, a survey was applied to determine students’ perceptions towards the use of scaffolding techniques. Assessing speaking performance rubric was used to evaluate speaking sub skills such as: grammar and vocabulary, discourse management, pronunciation and interactive communication. At the end of the investigation, the findings showed an improvement in students speaking development since the average before the treatment was 6,8/10, in contrast, after the treatments students’ average was 7,7/10. Thus, scaffolding techniques influence the speaking skill instudents of seventh semester from Pedagogía de los Idiomas Nacionales y Extranjeros atUniversidad Técnica de Ambato.